Dietary Fat Intake and Risk of Hepatocellular Carcinoma in Two Large Prospective Cohort Studies (FS13-07-19). (13th June 2019) - Yang, Wanshui; Sui, Jing; Ma, Yanan; Simon, Tracey G; Petrick, Jessica L; Lai, Michelle; McGlynn, Katherine A; Campbell, Peter T; Giovannucci, Edward; Chan, Andrew Tan; Zhang, Xuehong
Abstract: Objectives: Epidemiological evidence of an association between dietary fat intake and hepatocellular carcinoma (HCC) risk is limited and inconclusive, particularly from prospective studies. Methods: We prospectively examined intake of total and specific fats and major sources of dietary fats in relation to HCC risk within the Nurses' Health Study and the Health Professionals Follow-up Study. Dietary fats were measured at baseline and updated approximately every 4 years using validated food frequency questionnaires. Cox proportional hazards regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) after adjusting for potential confounders. Results: After an average follow-up of 28 years, 160 HCC cases including 85 women and 75 men were documented. According to food sources, there was a significant inverse association between vegetable fat intake and HCC risk (the highest vs. lowest quartile, HR = 0.61, 95% CI: 0.39–0.96, P trend = 0.02), but a suggestive positive association with animal or dairy fats. Replacing animal or dairy fats with an equivalent amount of vegetable fat was associated with a lower HCC risk (HR per 1-SD = 0.79, 95% CI: 0.65–0.97). According to fat subtypes, both monounsaturated and polyunsaturated fatty acids (PUFAs) including Omega-3 (the highest vs. lowest quartile, HR = 0.63, 95% CI: 0.41–0.96, P trend = 0.14) and Omega-6 PUFAs (HR = 0.54, 95% CI: 0.34–0.86, P trend = 0.02) were inversely associated with risk of HCC. The ratios of polyunsaturated and/or monounsaturated fat to saturated fat were all statistically inversely associated with HCC risk (all P trend ≤ 0.02). In addition, when replacing saturated fats with monounsaturated or polyunsaturated fats, the HR per 1-SD was 0.77 (95% CI: 0.64–0.92). Conclusions: Higher intake of vegetable fats and polyunsaturated fatty acids may be associated with lower HCC risk. Replacing animal or dairy fats with vegetable fats or replacing saturated fats with polyunsaturated or monounsaturated fats may reduce the risk of HCC among US adults. Funding Sources: This work was supported by grants from the National Institute of Health, American Cancer Society Research, Boston Nutrition Obesity Research Center Pilot and Feasibility Award.